Timeliness of financial reporting: Evidence from UAE - Al-Muzaiqer, Mohammed Ali Hussein; Ahmad, Maslina; Abdul Hamid, Fatima (2016)
The objective of this study is to examine the extent of audit report lag (ARL) in the United Arab Emirates (UAE). The ARL is well defined in the literature as the number of days between the date of the financial year end and the date of the audit report. The data of the study consists of 298 observations from listed companies on the UAE capital markets; Abu Dhabi Securities Exchange (ADX) and Dubai Financial Market (DFM), for three years from 2011 to 2013. Based on the sample data analyzed, the results show that listed companies in the UAE took on average of 60 days to announce their audited financial reports in 2011, 57 days in 2012 and 51 days in 2013, which are within the allowable period required by the regulators in UAE. Even though the overall result seems favorable, it is only based on 87%, 89% and 63% of companies whose annual reports are available on the websites of ADX and DFM for 2011, 2012 and 2013 respectively. These results perhaps indicate a low compliance of reporting requirements among listed companies in UAE. Since both markets can be considered new (established in 2000), monitoring of reporting requirement may not be as stringent as the established markets. As timely information release is necessary for effective investment decisions and a well-functioning financial market, the respective regulators should make it compulsory for the listed companies to announce their financial reports in the market’s website on timely basis and ensure that proper monitoring activities are in place.